Geochemistry of the Little Dal basalts: continental tholeiites from the Mackenzie Mountains, Northwest Territories, Canada - Dudás, Francis Ö.; Lustwerk, Rigel L. (Canadian Journal of Earth Sciences, 1997)
Analyses of the Little Dal lavas and the 779 Ma Tsezotene sills, both of the Mackenzie Mountains Supergroup, Northwest Territories, Canada, show them to be continental tholeiites that are geochemically related. The plagioclase- and clinopyroxene-phyric lavas are geochemically evolved and enriched in iron (up to 20.2 wt.% as Fe 2 O 3 ). Two magmatic lineages are identifiable and may represent different degrees of partial melting in the same source region, but cannot be related by fractional crystallization. Within each lineage, geochemical variation can be explained by fractional crystallization involving up to 60% crystallization of the original magma. The most evolved lavas occur at the base of the pile; less fractionated lavas occur toward the top of the sequence. The Nd isotopic composition of the Little Dal lavas averages ε = 1.4 at 780 Ma. Trace element and isotopic compositions are permissive of contamination by continental crust, but do not require a crustal component. The preserved volume of the Little Dal basalts is anomalously low (−100 km 3 ) compared with other Proterozoic continental tholeiites. There is considerable basaltic detritus in the sedimentary rocks of the overlying Coates Lake and Rapitan groups, and much of the original lava sequence may have been eroded. The Little Dal magmatic event is interpreted to be an early manifestation of rifting of North America from Australia.